Subclinical interstitial lung disease associated with rheumatoid arthritis - D V Bestaev (Терапевтический архив, 2014)
Interstitial lung disease (ILD) in rheumatoid arthritis (RA) is its extra-articular manifestation. At the same time, ILD considerably worsens the prognosis of the disease. Mortality rates for interstitial pulmonary fibrosis are 6% of all-cause mortality in RA patients. ILD can be identified by clinical examination only in 2-6% of cases, by plain chest X-ray in 1-6%, and by high-resolution computed tomography in 50-60%. The paper deals with subclinical ILD and discusses the state-of-the-art of investigations in this area.